2014
DOI: 10.1186/1475-2875-13-280
|View full text |Cite
|
Sign up to set email alerts
|

Imported malaria in a non-endemic area: the experience of the university of Campinas hospital in the Brazilian Southeast

Abstract: BackgroundAlthough malaria in Brazil almost exclusively occurs within the boundaries of the Amazon Region, some concerns are raised regarding imported malaria to non-endemic areas of the country, notably increased incidence of complications due to delayed diagnoses. However, although imported malaria in Brazil represents a major health problem, only a few studies have addressed this subject.MethodsA retrospective case series is presented in which 263 medical charts were analysed to investigate the clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(43 reference statements)
0
9
1
Order By: Relevance
“…6 However, in non-endemic areas, mainly due to the lack of previous immunity of the inhabitants and delayed diagnosis, this rate increases, and the occurrence of severe malaria in all age groups becomes a real concern. [5][6][7] The presence of mixed P. vivax and P. falciparum infections and the clinical course with several complications are the main aspects that need attention in the first case. Studies that compare the clinical and laboratory aspects between P. vivax or P. falciparum single infection and double infection suggest that coinfection is associated with different outcomes, including a lower probability of developing complications.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, in non-endemic areas, mainly due to the lack of previous immunity of the inhabitants and delayed diagnosis, this rate increases, and the occurrence of severe malaria in all age groups becomes a real concern. [5][6][7] The presence of mixed P. vivax and P. falciparum infections and the clinical course with several complications are the main aspects that need attention in the first case. Studies that compare the clinical and laboratory aspects between P. vivax or P. falciparum single infection and double infection suggest that coinfection is associated with different outcomes, including a lower probability of developing complications.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, median follow‐up time over than 28 days allowed confirmation of 20% of vivax malaria relapses, as these patients had not returned to transmission areas. Studies on imported malaria in Brazilian areas without transmission have reported relapse rates varying from 12.6 to 39.6% . However, these values should not be compared due to differences in study design and methods of monitoring antimalarial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on imported malaria in Brazilian areas without transmission have reported relapse rates varying from 12.6 to 39.6%. 15,16,47 However, these values should not be compared due to differences in study design and methods of mon- 2.94 times greater for patients with no primaquine dosing adjustments than for patients with primaquine dose adjustments. 15 A small sample size is one of the limitations of this study, which was due to the non-endemic study area.…”
Section: Discussionmentioning
confidence: 99%
“…For military personnel working in endemic areas, diarrhea was reported to be at a 50% prevalence ( He et al, 2013 ). Even in Brazilian travelers returning from the Amazon, diarrhea was reported at higher frequencies (67% for falciparum and 55% for vivax cases) ( Dos-Santos et al, 2014 ). Thus, diarrhea can be related to parasitemia and/or to acquired immunity.…”
Section: Discussionmentioning
confidence: 99%